Does Dapagliflozin influence arterial stiffness and levels of circulating anti-aging hormone soluble Klotho in people with type 2 diabetes and kidney disease? Results of a randomized parallel group clinical trial - Karalliedde, Janaka; Fountoulakis, Nikos; Stathi, Dimitra; Corcillo, Antonella; Flaquer, Maria; Panagiotou, Angeliki; Maltese, Giuseppe; Mangelis, Anastasios; Ayis, Salma; Gnudi, Luigi (Frontiers in Cardiovascular Medicine, 2022)
Objective The mechanisms that explain the cardio-renal benefits of sodium glucose co-transporter 2 (SGLT-2) inhibitors are unknown. The effect of SGLT-2 inhibitors on arterial aging, measured by Aortic Pulse Wave Velocity (Ao-PWV) and Soluble Klotho (s-Klotho), a circulating anti-aging biomarker of arterial health are also unclear. Design/Setting A 24-week single center randomized controlled trial (registry number/ EudraCT Number: 2013-004042-42) comparing Dapagliflozin and Ramipril (D+R) versus Ramipril (R) on the primary endpoint of urine albumin excretion rate (AER) and pre-specified secondary endpoints of Ao-PWV and biomarkers of arterial aging [s-Klotho and Fibroblast Growth Factor 23 (FGF-23)]. People with type 2 diabetes who had estimated glomerular filtration rate (eGFR) > 60 ml/min and residual microalbuminuria on maximum tolerated renin angiotensin system (RAS) inhibition were included in this study. Results In total, 33 participants (male 73%) were randomized to either D+R (n = 17) or R (n = 16) arms. After 24 weeks of treatment, Ao-PWV (mean ± SD) did not change significantly from baseline D +R [9.06 ± 1.91 m/s to 9.13 ± 2.03 m/s], and R [9.88 ± 2.12 m/s to 10.0 ± 1.84 m/s]. AER fell significantly by 43.5% (95% CI: −57.36%, −29.56%; p < 0.01) in people in the D+ R arm only. We do not observe any significant changes in FGF-23 or s-Klotho. HbA1c and Angiotensin 1–7 fell significantly only in D + R arm. Conclusions The combination of Dapagliflozin and Ramipril had no effects on Ao-PWV and s-Klotho which are biomarkers of arterial aging and cardio-renal risk. Our data suggest that the early cardio-renal benefits observed with SGLT-2 inhibitors are unlikely to be related to an improvement in arterial aging.